2022
DOI: 10.5187/jast.2022.e134
|View full text |Cite
|
Sign up to set email alerts
|

Estimating milk production losses by heat stress and its impacts on greenhouse gas emissions in Korean dairy farms

Abstract: Meteorological disasters caused by climate change like heat, cold waves, and unusually long rainy seasons affect the milk productivity of cows. Studies have been conducted on how milk productivity and milk compositions change due to heat stress (HS). However, the estimation of losses in milk production due to HS and hereby environmental impacts of greenhouse gas (GHG) emissions are yet to be evaluated in Korean dairy farms. Dairy milk production and milk compositions data from March to October 2018, provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Finally, the overall impact on milk production in the country is estimated at 2.68% and 10.02%, either using THI or THIa, respectively. These values are similar to those reported for three regions in Korea using THI(Park et al 2022). Martinsohn and Hansen (2012) reported that worldwide, only a narrow range of geographical and climatic zones has been considered regarding climate change impacts on the economics of dairy farming.The authors added that most studies dealing with climate change and dairy farming analyses either direct or indirect impacts.…”
supporting
confidence: 90%
“…Finally, the overall impact on milk production in the country is estimated at 2.68% and 10.02%, either using THI or THIa, respectively. These values are similar to those reported for three regions in Korea using THI(Park et al 2022). Martinsohn and Hansen (2012) reported that worldwide, only a narrow range of geographical and climatic zones has been considered regarding climate change impacts on the economics of dairy farming.The authors added that most studies dealing with climate change and dairy farming analyses either direct or indirect impacts.…”
supporting
confidence: 90%
“…Cows in this range have been reported to exhibit increased saliva production, respiration rate, water consumption, body temperature, and decreased feed intake. Studies have reported reduced milk protein, milk fat, and SNF levels due to heat stress [ 33 , 34 , 35 ]. Bohmanova et al [ 19 ] suggested that the decrease in milk components such as milk protein and milk fat, due to heat stress could be attributed to the dilution effect caused by decreased feed intake and increased water consumption.…”
Section: Resultsmentioning
confidence: 99%
“…improve the EB in the early period. To support these results, additional research will be needed in heat stress-associated consideration of the appropriate length of the dry period, party, and additives for milk production of dairy cows as well as greenhouse gas emission in the research of dairy science [34,35,36]. A C Ta = air temperature; RH = relative humidity; THI = temperature and humidity index.…”
Section: Discussionmentioning
confidence: 99%